Camellia sinensis Aqueous Extract: A Promising Candidate for Hepatic Eimeriosis Treatment in Rabbits - Hanadi B. A. Baghdadi; Mohamed Abdo Rizk (MDPI AG, 2023)
Eimeria stiedae (E. stiedae) is a common coccidian species that infects the liver and causes economic losses for the rabbit industry. This study aimed to determine the efficiency of green tea aqueous extract (GTE) as a natural treatment for eimeriosis caused by E. stiedae. Male rabbits Cuniculus L. (Oryctolagus) of the New Zealand White rabbit strain (4-4.5 months) were used, as they are suitable for research and conducting experiments. Thirty rabbits were allocated into six groups, with five rabbits in each group; the G1 group (non-infected untreated) served as a negative control group; the G2 group was not infected and treated with 250 mg GTE; the G3 group was not infected and treated with 500 mg GTE; the G4 group was untreated and was infected with 3 × 104 Sporulated E. stiedae oocysts, which served as a positive control group; the G5 group was infected and treated with 250 mg GTE; and the G6 group was infected and treated with 500 mg GTE. The hematological and biochemical analyses of each group of rabbit sera were carried out. Phytochemical analysis was performed to evaluate the active components in GTE leaves using the following methods: IR spectroscopy, liquid chromatography-mass spectrometry (LC-MS), energy-dispersive X-ray spectroscopy (EDX), and scanning electron microscopy. The infected rabbit groups treated with GTE at both doses of 250 and 500 mg/kg exhibited a significant decrease in the extent of E. stiedae oocyst shedding compared with the infected untreated group at 14, 21, and 28 days post-infection. Also, treatment with green tea showed improvement in liver weight compared with the enlarged livers of infected, untreated rabbits. The disturbance in serum liver enzymes' gamma-glutamyl transferase (GGT) and aspartate aminotransferase (AST/GOT) levels, as well as serum glucose, potassium, uric acid, cholesterol, and urea levels, were improved after the treatment of infected rabbit groups with green tea compared with the infected untreated group. Moreover, in this study, the images of the egg stages of the parasite were taken using a fluorescence microscope at 25 µm and 26 µm magnifications. This study provides promising results for the effective cell absorption of the aqueous extract of green tea, which was confirmed in the analyzed images using a scanning electron microscope at 5 µm and 20 µm magnifications.